Therapeutic vaccination strategies to treat nasopharyngeal carcinoma - Taylor, Graham S.; Steven, Neil M. (Chinese Clinical Oncology; Vol 5, No 2 (April 19, 2016): Chinese Clinical Oncology (Nasopharyngeal Carcinoma-Guest Editors: Joseph Wee, Yoke-Lim Soong, Melvin Chua), 2016)
Epstein-Barr virus (EBV) infects most people worldwide. EBV has oncogenic potential and is strongly associated with several lymphomas and carcinomas, including nasopharyngeal carcinoma (NPC), that together total 200,000 cases of cancer each year. All EBV-associated cancers express viral proteins that allow highly selective immunotherapeutic targeting of the malignant cells. A number of therapeutic EBV vaccines have been tested in clinical trials with evidence of immune boosting and clinical responses in NPC patients. Therapeutic vaccination could be used after adoptive T-cell transfer to increase and sustain the number of infused T-cells or combined with immunotherapies acting at different stages of the cancer immunity cycle to increase efficacy. The therapeutic EBV vaccines tested to date have been well tolerated with minimal off-target toxicity. A safe therapeutic vaccine that was also able to be mass produced could, in principle, be used to vaccinate large numbers of patients after first line therapy to reduce recurrence.